Pengaruh Motivasi dan Lingkungan Kerja Fisik Terhadap Kinerja Perawat Klinik Pratama Asshofwan - Awalia, Lia; Wanta; Hidayaty, Dwi Epty (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The performance of nurses determines the quality of health services. However, initial observations at Asshofwan Pratama Clinic showed a decrease in work morale and a lack of responsiveness of nurses in serving patients. This phenomenon indicates that there are problems in the aspects of work motivation and physical work environment that can have a direct impact on the performance of nurses. This study aims to explore in depth how these two factors affect nurse performance. The approach used is qualitative with a phenomenological study type. The data collection technique was carried out through in-depth interviews, non-participatory observations, and documentation of five nurses and one HRD party as informants. The results showed that nurses' work motivation was more influenced by intrinsic motivations, such as a sense of responsibility, and the satisfaction of seeing patients heal. The physical work environment is considered quite supportive, characterized by clean workspaces, adequate ventilation and lighting, and work facilities that are mostly complete although there are some tools that need to be updated. The performance of nurses in the clinic is considered good, reflected in discipline, precision, speed of work, and commitment to quality service strengthened by the theory of Self-Determination, Herzberg's Two-Factor Theory, and the WHO health worker performance model. This study suggests the need for increased non-financial support, innovation reform, and innovation facilitation to maintain and improve the performance of nurses in primary clinics.